Price escalation of unit rate of light weight concrete due to unusual increase in the price of cement (OPC Type) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the request for price escalation of unit rate of light weight concrete due to unusual increase in the price of cement for BRACU new campus project.